DELINEATION AND MAPPING OF ALLUVIAL FANS BY THE USE OF LANDSAT/TM AND TERRA/ASTER SATELLITE IMAGES. - Αστάρας, Θ.; Βουβαλίδης, Κ.; Οικονομίδης, Δ. (Bulletin of the Geological Society of Greece, 2018)
The purpose of the study was the precise delineation and mapping of alluvial fans, locating in mountainous areas of Northern Greece, by the use of: a) LANDSAT/TM and TERRA/ASTER satellite images (pixel size 30 m and 15-90 m respectively), b) topographic and geological maps and c) ground truth procedure (visiting the test sites). The digital processing of the satellite images was performed with EASI/PACE software. False Colour Composite (FCC) images, that helped to the better delineation of the fans, were derived by various image processing techniques, such as contrast stretching, ratioing, Principal Components Analysis (PCA),etc. The above processed images were imported into a Geographical Information System (GIS) and they were georeferenced to UTM Projection System. Next, the delineated (on the images) fans were digitized and overlaid to topographic and geological maps. From the above procedure and in comparison to ground-truth observations, it was concluded that the boundaries of the alluvial fans appear more precisely on the satellite images than in geological and topographic maps. The results of this study could be useful to geomorphologists dealing with morphological study and analysis of the alluvial fans. Also, they could be helpful to the improvement and updating of the present geological maps, by defining the boundaries of the fans mere precisely. Finally, conclusions can be drawn concerning the sorting of the materials comprising the fans. This information could be useful to hydrogeologists, since the alluvial fans are usually rich in water content.